2006
DOI: 10.3319/tao.2006.17.4.615(gh)
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Characters of Gas Hydrate Offshore of Southwestern Taiwan

Abstract: ABSTRACT1 Institute of Oceanography, National Taiwan University, Taipei, Taiwan, ROC 2 Central Geologic Survey, Taipei, Taiwan, ROC 3 Exploration Department, Chinese Petroleum Company, Miaoli, Taiwan, ROC * Corresponding author address: Prof. Char-Shine Liu, Institute of Oceanography, National Taiwan University, Taipei, Taiwan, ROC; E-mail: csliu@ntu.edu.tw Bottom simulating reflector (BSR) is a key indicator for the presence of gas hydrate beneath the sea floor. Widely distributed BSRs have been observed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(114 citation statements)
references
References 46 publications
4
108
1
1
Order By: Relevance
“…Geophysical surveys show that intensive Bottom Simulating Reflectors (BSRs), that are considered to be one of the most effective indicators of existing gas hydrate in a given region, are distributed in a wide area of offshore southwestern Taiwan (Chi et al 1998;Schnürle 1999Schnürle , 2002Liu et al 2004Liu et al , 2006. This indicates that abundant gas hydrate deposits may exist in the sediments of both the passive and active continental margins offshore of SW Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Geophysical surveys show that intensive Bottom Simulating Reflectors (BSRs), that are considered to be one of the most effective indicators of existing gas hydrate in a given region, are distributed in a wide area of offshore southwestern Taiwan (Chi et al 1998;Schnürle 1999Schnürle , 2002Liu et al 2004Liu et al , 2006. This indicates that abundant gas hydrate deposits may exist in the sediments of both the passive and active continental margins offshore of SW Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Based on seismic reflection profiles, they found many Bottom Simulating Reflections (BSRs) and concluded that gas hydrates are widely distributed under the seafloor of depths of 700 to 3000 m in this region (Chi et al 1998;Chow et al 2000;Schnürle et al 1999Schnürle et al , 2002Schnürle et al , 2006Liu et al 2006). The study presents the first systematic survey based on gas geochemical techniques performed in the gas hydrate area in offshore SW Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Sur- [28,30], seep community [31] and carbonate precipitation [26,29,32], high level of CH4 and H2S in sediments [31], mud diapir structures [33], seep carbonate precipitations and musselshell in site ROV-G Carbonate precipitations in core of ODP184-1146 [34], BSR in core's adjacent area [28], nature gas hydrate [35] and seep precipitations [27], high level of CH 4 in water column [36] Strike-slip faults, exploited oil/gas fields and cold seeps [37,38], oil/gas seeps [39], hydrocarbon anomaly [39,40], pyrite in sediments [41] Fold-thrust structures, BSR [42], pyrite and gypsum [41,43], methane-concentration enhancement beneath the seafloor [44], hydrocarbon anomaly [39,44] ; 8. Other prospective area in the SCS [39,40] face sediment samples were hermetically sealed in polythene bags after separation on board of the ship, and core sediment samples were preserved under room temperature.…”
Section: Sampling and Pretreatmentmentioning
confidence: 99%
“…Since the Mesozoic, the SCS went through a succession of geotectonic regimes and multiple faulted terraces and basins were formed with abundant organic matter. Under these temperature-pressure conditions, the SCS geological settings are in favor of gas hydrate formation and conservation [28][29][30]. Recently, a great deal of work about gas hydrate reservoirs has been done in the northern continental slope of SCS, and subsequently multiple lines of evidence related to gas hydrate were identified [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] (Table 1) and several prospective areas for gas hydrate occurrence were discovered and outlined (Figure 1).…”
mentioning
confidence: 99%